Quality of life outcomes from a randomized controlled trial of patient navigation in Latina breast cancer survivors. (26th September 2020) - Ramirez, Amelie G.; Muñoz, Edgar; Long Parma, Dorothy; Perez, Arely; Santillan, Alfredo
Abstract: Introduction: Breast cancer survivorship is a life‐long process involving challenges to health‐care communities and individuals, especially Latinas. Patient Navigation has shown some success in meeting these challenges. The purpose of this study was to compare the effects of an enhanced Patient Navigation program (Intervention; PN+) vs Control (PN) over time on general cancer and breast cancer‐specific quality of life (QoL) in Latina breast cancer survivors (BCS). Methods: We conducted a 2‐year, two‐arm randomized controlled trial of the "Staying Healthy" program among Latina BCS. The design compared PN+ vs PN over time. We recruited 60 patients into each study arm and randomized them by sequential numerical assignment. PN+ participants received culturally tailored educational materials and active, personalized Patient Navigation services, including phone calls, transportation, and care coordination. PN participants were navigated only upon request. Primary outcomes included general cancer (Functional Assessments of Cancer Therapy [FACTS]‐G) and breast cancer‐specific (FACT‐B) QoL. Results: PN+ participants had significantly improved QoL measures compared to PN at 6‐month follow‐up on all subscales ( P ‐values .007‐.04) except physical well‐being (PWB; P = .11). Intervention effect size coefficient (standard error) for FACT‐G overall was 7.9 (3.1); P = .01. For FACT‐B, it was 10.9 (3.9); P = .006. Again, all subscales showed significant effects [range 1.7‐3.1 (0.8‐1.2); P ‐values .006‐.04], except for PWB [1.5 (1.0); P = .16] and social/family well‐being (SWB) [2.1 (1.1); P = .06]. There were no differences between groups at baseline. Discussion: Multiple cultural, psychosocial, and socioeconomic variables contributing to these intervention effects will be addressed in future studies. As the national BCS population continues to increase, more Patient Navigation‐focused partnerships among patients, health‐care professionals, research groups, and community organizations are needed to improve BCS experiences. The Staying Healthy program has the potential to serve as a national survivorship care model for improving Latina BCS QoL. Abstract : We evaluated the effect of a two‐year, two‐arm randomized controlled trial (the "Staying Healthy" program) on quality of life (QoL) among Latina breast cancer survivors (BCS). The design compared enhanced Patient Navigation (Intervention; PN+) versus usual (Control; PN) over time. PN+ participants had significantly improved quality of life measures compared to PN at 6‐month follow‐up.